Preparation method of high-performance molybdenum alloy based on composite additive manufacturing process

By adding toughened metal particles to molybdenum powder and combining thermal isostatic pressing technology, the problem of cracks and holes of molybdenum alloy in the melting of laser powder bed is solved, and its mechanical properties and density are significantly improved, and high-performance molybdenum alloy is prepared. .

CN119260021APending Publication Date: 2025-01-07HENAN ACAD OF SCI CARBON MATRIX COMPOSITES RES INST

Patent Information

Application Number
CN202411305657.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In traditional processing methods, molybdenum and its alloys are prone to defects such as cracks and holes, which affects their mechanical properties. In addition, molybdenum alloys prepared by traditional powder metallurgy have problems such as coarse grains and poor finished product quality, which is difficult to meet the needs of high-performance materials.

Method used

Combined with thermal isostatic pressing technology and laser powder bed melting technology, by adding toughened metal particles to molybdenum powder and performing three-dimensional vibration and stirring, the laser powder bed is melted and printed and thermal isostatic pressing is performed to eliminate cracks and holes and improve tissue structure. , improve density and mechanical properties.

Benefits of technology

It effectively eliminates cracks and holes generated in the melting of laser powder beds, significantly improves the tensile strength and elongation of molybdenum alloy, improves its mechanical properties and density, and prepares high-performance molybdenum alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119260021A_ABST
    Figure CN119260021A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of metal materials, in particular to a preparation method of a high-performance molybdenum alloy based on a composite additive manufacturing process. According to the method, the toughened metal particles are added into the molybdenum alloy, so that cracks generated by the molybdenum alloy in laser powder bed melting can be effectively eliminated, and the novel crack-free molybdenum alloy is prepared. Meanwhile, the hot isostatic pressing technology is used for further reducing holes in the novel crack-free molybdenum alloy and improving the organization structure, so that the mechanical property of the novel crack-free molybdenum alloy is improved, and the molybdenum alloy with high compactness and high performance is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal materials, and in particular to a method for preparing a high-performance molybdenum alloy based on a composite additive manufacturing process. Background Art

[0002] Molybdenum has a strong interatomic bonding force, and has the characteristics of high melting point, low expansion coefficient, high conductivity, high stability at room temperature, and strong corrosion resistance. Therefore, it and its alloys are widely used in many occasions, such as lighting, electrical and electronic equipment, medical equipment, material processing equipment, high-temperature furnaces and related equipment, thermal spray coatings, aviation and defense components, etc. All of the above application fields require materials to have a combination of multiple properties. Molybdenum and its alloys, because they can provide a unique combination of multiple properties, have become ideal manufacturing materials in these fields and have good development prospects.

[0003] Molybdenum and its alloys also have certain disadvantages, such as room temperature brittleness, high toughness-brittle transition temperature and low recrystallization temperature. The above disadvantages make it difficult to have long cycle, poor quality of finished products and high cost in traditional processing. The traditional method of using powder metallurgy is prone to coarse grains and defects such as holes and inclusions, which will seriously reduce the mechanical properties of molybdenum alloys. Therefore, it is of great significance to use advanced manufacturing technology to efficiently prepare high-performance molybdenum alloys. And this technology needs to have high flexibility, short production cycle and low manufacturing cost, so as to further improve the applicability of molybdenum alloys in application fields. Summary of the invention

[0004] At present, laser powder bed melting has been used to prepare high-strength, high-melting-point, and difficult-to-process refractory alloys (mainly including tantalum, tungsten, and molybdenum metals). However, due to the brittleness and low grain boundary strength of molybdenum itself, it is very easy to crack at the high cooling rate in laser powder bed melting, and holes will be generated due to improper input laser energy. These defects will seriously affect the mechanical properties of molybdenum alloys.

[0005] The main purpose of the present invention is to combine hot isostatic pressing technology with laser powder bed melting technology to eliminate the defects generated when laser powder bed melting is used to process molybdenum and its alloys. While eliminating the defects, the original shape of the parts is not changed, and the organization can be improved, thereby improving the density and mechanical properties of the parts, thereby solving the technical problems of the prior art that cracks and holes are prone to occur when processing molybdenum alloys and the performance is low.

[0006] To achieve the above object, the present invention provides a method for preparing a high-performance molybdenum alloy based on a composite additive manufacturing process, the steps of which are as follows:

[0007] S1. Prepare molybdenum powder for printing;

[0008] S2. Add toughening metal particles into the molybdenum powder to obtain a molybdenum mixed powder;

[0009] S3. Use a three-dimensional vibration mixer to mix the molybdenum mixed powder thoroughly;

[0010] S4. Printing the molybdenum mixed powder into a crack-free molybdenum alloy by laser powder bed fusion technology;

[0011] S5. Use hot isostatic pressing technology to post-treat crack-free molybdenum alloy to produce high-performance molybdenum alloy.

[0012] As an improvement, the particle size of the molybdenum powder is 15-53 μm, and the composition of the molybdenum powder includes

[0013] O, C, S, Al, Ca, Cu, Mn, Ni, Na, Zn, Fe, W and Mo.

[0014] As an improvement, the contents of the components of the molybdenum powder are respectively:

[0015] O: 248ppm;

[0016] C: 0.0086wt.%;

[0017] S: <0.0060wt.%;

[0018] Al: <0.0012wt.%;

[0019] Ca: 0.0017wt.%;

[0020] Cu: 0.0045wt.%;

[0021] Mn: <0.001wt.%;

[0022] Ni: <0.001wt.%;

[0023] Na: 0.0028wt.%;

[0024] Zn: 0.0011wt.%;

[0025] Fe: 0.002wt.%;

[0026] W: 0.0036wt.%;

[0027] Mo:>99.9wt.%.

[0028] As an improvement, the toughening metal particles are one of titanium, rhenium, zirconium and tantalum;

[0029] The particle size of the toughening metal particles is 4-25 μm, and the content of the toughening metal particles accounts for 0.4-20 wt.% of the molybdenum mixed powder.

[0030] As an improvement, the molybdenum mixed powder is placed in a three-dimensional vibration mixer under an argon atmosphere, and the molybdenum mixed powder is stirred at a set speed and for a set time to fully mix the molybdenum powder and the toughening metal particles;

[0031] The purity of argon in the argon atmosphere is ≥99.99%, the set rotation speed is 60-210 r / min, and the set time is 1-11 hours.

[0032] As an improvement, in an argon atmosphere, a model to be printed is imported into a printer using laser powder bed fusion technology, and the molybdenum mixed powder that is fully mixed and uniform is printed according to the set printing parameters corresponding to the printer to obtain the crack-free molybdenum alloy;

[0033] The printing parameters include laser power, laser scanning speed, laser scanning spacing, thickness between powder layers, filling method, scanning method, substrate heating temperature and single / double laser scanning;

[0034] The purity of argon in the argon atmosphere is ≥99.99%, the laser power is 150-350W, the laser scanning speed is 150-450mm / s, the laser scanning interval is 0.05-0.11mm, the thickness between the powder layers is 0.015-0.065mm, the filling method is overall filling, the scanning method is an S-shaped scanning with a rotation angle of 60-90° between adjacent layers, the substrate heating temperature is 100-250℃, and the single / dual laser scanning is a single laser scanning or a dual laser remelting scanning.

[0035] As an improvement, the crack-free molybdenum alloy is placed in a hot isostatic press, and after the vacuum is evacuated to a set vacuum degree using a vacuum pump, argon gas is introduced to clean the furnace, and the pressurization rate is controlled to increase the pressure using argon gas as a medium, and the temperature is increased by controlling the heating rate, and the set temperature is reached at the same time as the set pressure, and the temperature is maintained for a set time. A cooling process is selected and the cooling rate is controlled to cool to room temperature, and the exhaust rate is controlled to exhaust argon gas and reduce the pressure, so as to obtain the high-performance molybdenum alloy;

[0036] The set vacuum degree is ≤10 -4 Pa, the purity of the argon gas is ≥99.999%, the pressurization rate is 10-20 bar / min, the set pressure is 140-160 MPa, the set temperature is 1000-1200°C, the set time is 2-3h, the cooling process is low-temperature nitrogen flow cooling, the cooling rate is ≤10°C / min, and the exhaust rate is ≤4L / min;

[0037] The method for controlling the heating rate is: first increase the temperature to a designated temperature node at 6-10°C / min, and then increase the temperature to a set temperature at 2-5°C / min, wherein the temperature of the designated temperature node is 50-60°C lower than the set temperature.

[0038] As an improvement, there are no cracks in the crack-free molybdenum alloy, its porosity is ≤1%, and its tensile strength and elongation are 286±32MPa and 0.08±0.02% respectively.

[0039] As an improvement, there are no cracks in the high-performance molybdenum alloy, its porosity is ≤0.5%, and its tensile strength and elongation are 598±22MPa and 0.18±0.02% respectively.

[0040] The technical advantages of the present invention are:

[0041] The present invention can effectively eliminate cracks generated in the molybdenum alloy during laser powder bed melting by adding toughening metal particles to the molybdenum alloy, thereby preparing a new crack-free molybdenum alloy. At the same time, the present invention uses hot isostatic pressing technology to further reduce the pores inside the new crack-free molybdenum alloy, improve the organizational structure, thereby improving its mechanical properties, and preparing a high-density and high-performance molybdenum alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a schematic flow chart of an embodiment of a method for preparing a high-performance molybdenum alloy based on a composite additive manufacturing process of the present invention;

[0043] Figure 2 Surface morphology of the new high-performance molybdenum alloy, the new crack-free molybdenum alloy and the traditional molybdenum alloy prepared by the present invention;

[0044] Figure 3 EPMA test results of the new high-performance molybdenum alloy and the new crack-free molybdenum alloy of the present invention

[0045] Figure 4 Schematic diagram of room temperature tensile stress-strain curves of the novel high-performance molybdenum alloy and the novel crack-free molybdenum alloy of the present invention;

[0046] Figure 5 The lattice structure parts are prepared by the preparation method of the high-performance molybdenum alloy based on the composite additive manufacturing process of the present invention. DETAILED DESCRIPTION

[0047] The present invention is described in detail and specifically by specific examples below to provide a better understanding of the present invention, but the following examples do not limit the protection scope of the present invention.

[0048] Example

[0049] The present invention provides a method for preparing a high-performance molybdenum alloy based on a composite additive manufacturing process, referring to Figure 1 , Figure 1 It is a schematic diagram of a process of an embodiment of the preparation method of the present invention.

[0050] In this embodiment, the preparation method is as follows:

[0051] Step S1, preparing molybdenum powder with qualified purity for printing;

[0052] In this embodiment, molybdenum powder is molybdenum powder, which contains molybdenum and trace amounts of other elements. It should be noted that the molybdenum powder does not contain titanium, rhenium, zirconium, or tantalum.

[0053] Further, the molybdenum powder contains elements such as O (oxygen), C (carbon), S (sulfur), Al (aluminum), Ca (calcium), Cu (copper), Mn (manganese), Ni (nickel), Na (sodium), Zn (zinc), Fe (iron), W (tungsten) and Mo (molybdenum), and the particle size of the molybdenum powder is 15-53 μm;

[0054] The contents of each component of molybdenum powder are:

[0055] O: 248ppm; C: 0.0086wt.%; S: <0.0060wt.%; Al: <0.0012wt.%; Ca: 0.0017wt.%; Cu: 0.0045wt.%; Mn: <0.00 1wt.%; Ni: <0.001wt.%; Na: 0.0028wt.%; Zn: 0.0011wt.%; Fe: 0.002wt.%; W: 0.0036wt.%; Mo: >99.9wt.%.

[0056] Step S2, mixing a certain amount of toughening metal particles into molybdenum powder to obtain molybdenum mixed powder;

[0057] The toughening metal particles are one of titanium, rhenium, zirconium and tantalum; the particle size is 4-25 μm, and the content of the toughening metal particles accounts for 0.4-20 wt.% of the weight percentage of the molybdenum mixed powder.

[0058] Molybdenum mixed powder is the raw material required for the subsequent preparation of new crack-free molybdenum alloy. Adding toughening metal particles to molybdenum powder can effectively toughen the molybdenum alloy.

[0059] Step S3, using a three-dimensional vibration mixer to fully mix the molybdenum mixed powder.

[0060] Since the molybdenum mixed powder will generate high temperature during the stirring process, it is possible that the molybdenum mixed powder will be oxidized and introduce O element. The increase of O element will make the formed molybdenum alloy brittle and affect the quality of printing. Therefore, the protection of argon atmosphere is required when stirring the molybdenum mixed powder.

[0061] In this embodiment, the molybdenum mixed powder is stirred in an argon protective atmosphere by a three-dimensional vibration stirrer according to a set speed and time. The purity of argon in the argon atmosphere is ≥99.99%; the speed during stirring is 60-210 r / min, and the stirring time is 1-11 hours.

[0062] Step S4, using laser powder bed fusion technology, printing the molybdenum mixed powder according to preset printing parameters to obtain a new crack-free molybdenum alloy.

[0063] In this embodiment, the molybdenum mixed powder is evenly mixed and printed by laser powder bed melting technology. The introduced toughening metal particles can strengthen the molybdenum alloy matrix, thereby printing a new type of crack-free molybdenum alloy.

[0064] Printing parameters include laser power, laser scanning speed, laser scanning spacing, thickness between powder layers, filling method, scanning method, substrate heating temperature and single / dual laser scanning;

[0065] Printing is carried out in an argon atmosphere, and the purity of argon in the argon atmosphere is ≥99.99%. During printing, the laser power is 150-350W, the laser scanning speed is 150-450mm / s, the laser scanning spacing is 0.05-0.11mm, and the thickness between powder layers is 0.015-0.065mm.

[0066] This embodiment adopts the filling method of overall filling during printing, the scanning method is S-shaped scanning with an angle of 60-90° between adjacent layers, the heating temperature of the substrate is 100-250°C, and the single / double laser scanning is single laser scanning or double laser remelting scanning.

[0067] Step S5, using hot isostatic pressing technology to post-process the new crack-free molybdenum alloy according to the set pressure, temperature and time to obtain a new high-performance molybdenum alloy.

[0068] In this embodiment, although the molybdenum alloy with toughening metal particles added avoids the generation of cracks in laser powder bed melting, it still has the defects of holes and low performance. Therefore, it is necessary to use hot isostatic pressing to post-process the formed molybdenum alloy. Under the high temperature and high pressure environment of hot isostatic pressing, the holes in the formed molybdenum alloy can be reduced to a certain extent, the structural organization can be improved, and then it is beneficial to improve the density and mechanical properties of the molybdenum alloy, and prepare a new high-performance molybdenum alloy.

[0069] The specific method of hot isostatic pressing is as follows: placing a crack-free molybdenum alloy in a hot isostatic press, using a vacuum pump to evacuate to a set vacuum degree, introducing argon gas to clean the furnace, using argon gas as a medium to control the pressurization rate to increase the pressure, controlling the heating rate to increase the temperature, reaching the set temperature and the set pressure at the same time, keeping the temperature and pressure for a set time, selecting a cooling process and controlling the cooling rate to cool to room temperature, controlling the exhaust rate to exhaust the argon gas and reduce the pressure, and obtaining a high-performance molybdenum alloy;

[0070] The vacuum degree is set to ≤10 -4 Pa, the purity of argon is ≥99.999%, the pressurization rate is 10-20bar / min, the set pressure is 140-160MPa, the set temperature is 1000-1200℃, the set time is 2-3h, the cooling process is low-temperature nitrogen flow cooling, the cooling rate is ≤10℃ / min, and the exhaust rate is ≤4L / min;

[0071] The method for controlling the heating rate is: first increase the temperature to the specified temperature node at 6-10°C / min, and then increase the temperature to the set temperature at 2-5°C / min. The temperature of the specified temperature node is 50-60°C lower than the set temperature.

[0072] like Figure 2 The surface morphology of the traditional molybdenum alloy (Pure Mo), the new crack-free molybdenum alloy (As-built) and the new high-performance molybdenum alloy (HIP) are shown in Figure 2. There are a large number of cracks and holes on the surface of the Pure Mo sample, which will seriously affect the density of the molybdenum alloy, and these defects can easily become crack sources and reduce the mechanical properties of the molybdenum alloy. The As-built sample with the addition of titanium particles (or any one of rhenium, zirconium, and tantalum) eliminates the cracks, but there are still a small number of smaller holes on the surface. The HIP sample after hot isostatic pressing reduces the porosity from 0.27% to 0.22%, indicating that hot isostatic pressing can reduce the defects of the molybdenum alloy to a certain extent, which will improve the mechanical properties of the molybdenum alloy.

[0073] like Figure 3 The EPMA test results of As-built and HIP samples. In the As-built sample, there is an uneven distribution of elements. The Mo content in Region 1 is high, while the Ti content is low, and there is incompletely diffused Ti element. This is because the solute atoms do not have enough time to fully diffuse in the Mo matrix at the high cooling rate in laser powder bed melting. In the HIP sample, the high temperature and high pressure of hot isostatic pressing give the solute atoms enough energy and sufficient time to diffuse, so that the elements are evenly distributed, which is beneficial to improving the mechanical properties of molybdenum alloys, indicating that hot isostatic pressing can improve the uniformity of element distribution in molybdenum alloys.

[0074] The preparation method of high-performance molybdenum alloy based on composite additive manufacturing process proposed in this embodiment is to obtain molybdenum powder with qualified purity for printing; mix a certain amount of titanium particles (or any one of rhenium, zirconium and tantalum) into the molybdenum powder to obtain a molybdenum mixed powder; use a three-dimensional vibration mixer to fully mix the molybdenum mixed powder; use laser powder bed melting technology to print the molybdenum mixed powder according to preset printing parameters to obtain a new crack-free molybdenum alloy; use hot isostatic pressing technology to post-process the new crack-free molybdenum alloy according to the set pressure, temperature and duration to obtain a new high-performance molybdenum alloy. The present invention eliminates the thermal cracks generated by the molybdenum alloy in the laser powder bed melting by adding titanium (or any one of rhenium, zirconium and tantalum) to the molybdenum alloy, and then uses hot isostatic pressing to further reduce the holes inside the new crack-free molybdenum alloy, improve the organizational structure, thereby improving its mechanical properties, and preparing a high-density and high-performance molybdenum alloy.

[0075] Furthermore, the tensile properties of the As-built and HIP samples were tested respectively, and the tensile strength and elongation were tested using a universal mechanical testing machine. Figure 4 The room temperature tensile curves of As-built and HIP samples are shown. The tensile strength of As-built sample is 286±32MPa and the elongation is 0.08±0.02%. After hot isostatic pressing, the tensile strength and elongation are increased to 598±22MPa and 0.18±0.02%, respectively, an increase of 109% and 125%, respectively. Its tensile strength is higher than that of pure molybdenum (CP-Mo: 534MPa).

[0076] like Figure 5 The lattice structure parts are prepared by the preparation method of high-performance molybdenum alloy based on the composite additive manufacturing process. It can be seen that this preparation method can not only prepare high-performance molybdenum alloys, but also be used to produce complex parts that are difficult to manufacture or process by traditional methods. This will be beneficial to improve the applicability of molybdenum alloys in their core fields.

[0077] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

[0078] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not equivalent to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention.

Claims

1. A method for preparing a high-performance molybdenum alloy based on a composite additive manufacturing process, characterized in that: The preparation method is as follows: S1. Prepare molybdenum powder for printing; S2. Add toughening metal particles into the molybdenum powder to obtain a molybdenum mixed powder; S3. Use a three-dimensional vibration mixer to mix the molybdenum mixed powder thoroughly; S4. Printing the molybdenum mixed powder into a crack-free molybdenum alloy by laser powder bed fusion technology; S5. Use hot isostatic pressing technology to post-treat crack-free molybdenum alloy to produce high-performance molybdenum alloy.

2. The method for preparing a high-performance molybdenum alloy based on a composite additive manufacturing process according to claim 1, characterized in that: The particle size of the molybdenum powder is 15-53 μm, and the composition of the molybdenum powder includes O, C, S, Al, Ca, Cu, Mn, Ni, Na, Zn, Fe, W and Mo.

3. The method for preparing a high-performance molybdenum alloy based on a composite additive manufacturing process according to claim 2, characterized in that: The contents of the components of the molybdenum powder are respectively: O: 248ppm; C: 0.0086wt.%; S: <0.0060wt.%; Al: <0.0012wt.%; Ca: 0.0017wt.%; Cu: 0.0045wt.%; Mn: <0.001wt.%; Ni: <0.001wt.%; Na: 0.0028wt.%; Zn: 0.0011wt.%; Fe: 0.002wt.%; W: 0.0036wt.%; Mo:>99.9wt.%.

4. The method for preparing a high-performance molybdenum alloy based on a composite additive manufacturing process according to claim 1, characterized in that: The toughening metal particles are one of titanium, rhenium, zirconium and tantalum; The particle size of the toughening metal particles is 4-25 μm, and the content of the toughening metal particles accounts for 0.4-20 wt.% of the molybdenum mixed powder.

5. The method for preparing a high-performance molybdenum alloy based on a composite additive manufacturing process according to claim 1, characterized in that: Placing the molybdenum mixed powder in a three-dimensional vibration mixer under an argon atmosphere, stirring the molybdenum mixed powder at a set speed and for a set time, and fully mixing the molybdenum powder and the toughening metal particles; The purity of argon in the argon atmosphere is ≥99.99%, the set rotation speed is 60-210 r / min, and the set time is 1-11 hours.

6. The method for preparing a high-performance molybdenum alloy based on a composite additive manufacturing process according to claim 1, characterized in that: In an argon atmosphere, a model to be printed is imported into a printer using laser powder bed fusion technology, and the molybdenum mixed powder that is fully mixed and uniform is printed according to the set printing parameters corresponding to the printer to obtain the crack-free molybdenum alloy; The printing parameters include laser power, laser scanning speed, laser scanning spacing, thickness between powder layers, filling method, scanning method, substrate heating temperature and single / double laser scanning; The purity of argon in the argon atmosphere is ≥99.99%, the laser power is 150-350W, the laser scanning speed is 150-450mm / s, the laser scanning interval is 0.05-0.11mm, the thickness between the powder layers is 0.015-0.065mm, the filling method is overall filling, the scanning method is an S-shaped scanning with a rotation angle of 60-90° between adjacent layers, the substrate heating temperature is 100-250℃, and the single / dual laser scanning is a single laser scanning or a dual laser remelting scanning.

7. The method for preparing a high-performance molybdenum alloy based on a composite additive manufacturing process according to claim 1, characterized in that: The crack-free molybdenum alloy is placed in a hot isostatic press, and after the vacuum is evacuated to a set vacuum degree using a vacuum pump, argon gas is introduced to clean the furnace, and the pressurization rate is controlled to increase the pressure using argon gas as a medium, and the temperature is increased by controlling the heating rate, and the set temperature is reached at the same time as the set pressure, and the temperature is maintained for a set time, and the cooling process is selected and the cooling rate is controlled to cool to room temperature, and the exhaust rate is controlled to exhaust the argon gas and reduce the pressure, so as to obtain the high-performance molybdenum alloy; The set vacuum degree is ≤10 -4 Pa, the purity of the argon gas is ≥99.999%, the pressurization rate is 10-20 bar / min, the set pressure is 140-160 MPa, the set temperature is 1000-1200°C, the set time is 2-3h, the cooling process is low-temperature nitrogen flow cooling, the cooling rate is ≤10°C / min, and the exhaust rate is ≤4L / min; The method for controlling the heating rate is: first increase the temperature to a designated temperature node at 6-10°C / min, and then increase the temperature to a set temperature at 2-5°C / min, wherein the temperature of the designated temperature node is 50-60°C lower than the set temperature.

8. The method for preparing a high-performance molybdenum alloy based on a composite additive manufacturing process according to claim 1, characterized in that: The crack-free molybdenum alloy has no cracks, a porosity of ≤1%, and tensile strength and elongation of 286±32 MPa and 0.08±0.02% respectively.

9. The method for preparing a high-performance molybdenum alloy based on a composite additive manufacturing process according to claim 1, characterized in that: There are no cracks in the high-performance molybdenum alloy, the porosity of which is ≤0.5%, and the tensile strength and elongation are 598±22MPa and 0.18±0.02% respectively.

Citation Information

Patent Citations

  • Method for purifying molybdenum powder

    CN101347839A

  • Preparation method for molybdenum and molybdenum alloy part

    CN105798295A

  • Preparation method of molybdenum metal grille

    CN109014230A

  • Novel high-performance molybdenum alloy and preparation method thereof

    CN113637884A

  • Preparation method of molybdenum alloy tube target material, molybdenum alloy tube target material and application

    CN114939661A

Cited By

  • Laser additive manufacturing method for high-density low-defect molybdenum-rhenium alloy part

    CN120984900A

  • Additive manufacturing method of high-plasticity molybdenum-rhenium alloy

    CN121423634A